21.3k views
1 vote
For each quadratic expression below, drag an equivalent expression to its match

For each quadratic expression below, drag an equivalent expression to its match-example-1
User Jrummell
by
5.2k points

1 Answer

1 vote

1. Given the expression:


\mleft(x+2\mright)\mleft(x-4\mright)

You can use the FOIL method to multiply the binomials. Remember that the FOIL method is:


(a+b)\mleft(c+d\mright)=ac+ad+bc+bd

Then, you get:


\begin{gathered} =(x)(x)-(x)(4)+(2)(x)-(2)(4) \\ =x^2-4x+2x^{}-8 \end{gathered}

Adding the like terms, you get:


=x^2-2x-8

2. Given:


x^2-6x+5

You have to complete the square:

- Identify the coefficient of the x-term". In this case, this is -6.

- Divide -6 by 2 and square the result:


((-6)/(2))^2=(-3)^2=9

- Now add 9 to the polynomial and also subtract 9 from the polynomial:


=x^2-6x+(9)+5-(9)

- Finally, simplifying and completing the square, you get:


=(x-3)^2-4

3. Given the expression:


\mleft(x+3\mright)^2-7

You can simplify it as follows:

- Apply:


(a+b)^2=a^2+2ab+b^2

In this case:


\begin{gathered} a=x \\ b=3 \end{gathered}

Then:


\begin{gathered} =\lbrack(x)^2+(2)(x)(3)+(3)^2\rbrack-7 \\ =\lbrack x^2+6x+9\rbrack-7 \end{gathered}

- Adding the like terms, you get:


=x^2+6x+2

4. Given:


x^2-8x+15

You need to complete the square by following the procedure used in expression 2.

In this case, the coefficient of the x-term is:


b=-8

Then:


((-8)/(2))^2=(-4)^2=16

By Completing the square, you get:


\begin{gathered} =x^2-8x+(16)+15-(16) \\ =(x-4)^2-1 \end{gathered}

Therefore, the answer is:

For each quadratic expression below, drag an equivalent expression to its match-example-1
User Gre Hahn
by
4.7k points